At the center of it all : scaffolding Advanced information Literacies for K-12 Students in School Libraries - Michelle Schira Hagerman (2014)
The Burning Question - How do we teach students to develop the advanced literacies skills that will allow them to thrive in a complex, and ever-changing landscape of literacy?
Keywords: compétences; lecture numérique

Digging Deeper : Online Reading Comprehension and Collaborative Inquiry. Providence - Julie Coiro; Michelle Schira Hagerman (RI : Summer Institute on Digital Literacy, 2013)
Keywords: compétences; jeunesse; lecture numérique